Early predictors of intensive care unit admission among COVID-19 patients in Qatar - Abuyousef, Safae; Alnaimi, Shaikha; Omar, Nabil E.; Elajez, Reem; Elmekaty, Eman; Abdelfattah-Arafa, Eiman; Barazi, Raja; Ghasoub, Rola; Rahhal, Ala; Hamou, Fatima; Al-Amri, Maha; Karawia, Ahmed; et al. (Frontiers in Public Health, 2024)
Background COVID-19 is associated with significant morbidity and mortality. This study aimed to explore the early predictors of intensive care unit (ICU) admission among patients with COVID-19. Methods This was a case–control study of adult patients with confirmed COVID-19. Cases were defined as patients admitted to ICU during the period February 29–May 29, 2020. For each case enrolled, one control was matched by age and gender. Results A total of 1,560 patients with confirmed COVID-19 were included. Each group included 780 patients with a predominant male gender (89.7%) and a median age of 49 years (interquartile range = 18). Predictors independently associated with ICU admission were cardiovascular disease (adjusted odds ratio (aOR) = 1.64, 95% confidence interval (CI): 1.16–2.32, p = 0.005), diabetes (aOR = 1.52, 95% CI: 1.08–2.13, p = 0.016), obesity (aOR = 1.46, 95% CI: 1.03–2.08, p = 0.034), lymphopenia (aOR = 2.69, 95% CI: 1.80–4.02, p < 0.001), high AST (aOR = 2.59, 95% CI: 1.53–4.36, p < 0.001), high ferritin (aOR = 1.96, 95% CI: 1.40–2.74, p < 0.001), high CRP (aOR = 4.09, 95% CI: 2.81–5.96, p < 0.001), and dyspnea (aOR = 2.50, 95% CI: 1.77–3.54, p < 0.001). Conclusion Having cardiovascular disease, diabetes, obesity, lymphopenia, dyspnea, and increased AST, ferritin, and CRP were independent predictors for ICU admission in patients with COVID-19.